2017
DOI: 10.1371/journal.pntd.0005826
|View full text |Cite|
|
Sign up to set email alerts
|

The microbiome in urogenital schistosomiasis and induced bladder pathologies

Abstract: BackgroundHuman schistosomiasis is a highly prevalent neglected tropical disease (NTD) caused by Schistosoma species. Research on the molecular mechanisms influencing the outcomes of bladder infection by Schistosoma haematobium is urgently needed to develop new diagnostics, therapeutics and infection prevention strategies. The objective of the research study was to determine the microbiome features and changes in urine during urogenital schistosomiasis and induced bladder pathologies.MethodologySeventy partici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 62 publications
1
36
0
1
Order By: Relevance
“…Recent studies on the mechanisms of tumour development in schistosomiasis have highlighted the role of estrogen-related molecules from the parasite, as such molecules were found in many urine samples from infected persons in Angola [ 8 , 9 , 10 ]. Also, it was recently shown that an inflammation-regulatory microbiome could play important roles in the maintenance or development of bladder pathologies during infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies on the mechanisms of tumour development in schistosomiasis have highlighted the role of estrogen-related molecules from the parasite, as such molecules were found in many urine samples from infected persons in Angola [ 8 , 9 , 10 ]. Also, it was recently shown that an inflammation-regulatory microbiome could play important roles in the maintenance or development of bladder pathologies during infection [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, research has shown that this is not the case and that the urinary tract is in fact, another site with a microbiome, reflective of the microbes inhabiting the bladder and closely associated organs (Wolfe et al, 2012; Siddiqui et al, 2012; Whiteside et al; 2015). This evidence is supported by enhanced quantitative cultures, 16S marker studies and metagenomics, in different populations (e.g Kramer et al, 2018; Adebayo et al, 2017;Wu et al, 2017).…”
Section: Introductionmentioning
confidence: 70%
“…However, given the insufficiency of these hypotheses to explain the occurrence of cancer in the smallest part of the parasitized patients, more recent studies explore the auxiliary role of gastric, colorectal, and urogenital microbiomes ( 15 19 ).…”
Section: Helminths and Human Cancersmentioning
confidence: 99%
“…In addition, Adebayo and colleagues ( 15 ) studied the urinary microbiome during S. haematobium infection and demonstrated that specific microorganisms are associated with both inflammation and host protection ( 15 ). They noted that Proteobacteria and Firmicutes dominated the microbiome of both non-infected persons and persons with urogenital schistosomiasis.…”
Section: Helminths and Human Cancersmentioning
confidence: 99%
See 1 more Smart Citation